From Evidence to Policy Supporting Nepal’s Trade Integration Strategy : Assessment of the Impact of the Cash Incentive to Promote Export Diversification in Nepal - Pazzini, Aldo (World Bank, Washington, DC, 2016)
In 2010 or 2011, Nepal set up a cash incentive scheme for exporters aimed at reducing its trade deficit and vulnerability to external shocks, by promoting export growth and diversification for its firms. The Trade and Competitiveness Global Practice has been partnering with the Government of Nepal to assess the impact of the cash incentive program on export growth and diversification. This note presents the main results of the analysis. Making the support to firms’ internationalization a policy priority is commendable Countries around the world, and many countries in the South Asia region have incentives in place to help firms become exporters and succeed in diversifying their export markets.But not all interventions designed to support firms’ internationalization work, so, evaluating impact is crucial.Some of the planned changes in the scheme introduced in 2013 revealed public-private dialogue. However, many of these changes have not been fully implemented. The fast-track system introduced in 2013, and by which, firms exporting priority products would not need to certify domestic value addition reflect the systematic feedback of the private sector on the complexity of proving value added content.At the firm level there is no evidence showing a clear link between the effective incentive rates received and export performance, or the changes in the export incentive scheme and performance. The main policy conclusion that emerges from this analysis is that the current incentive scheme needs to be revised. The rest of the note is structured as follows. Section two discusses aspects of the design of the allocation mechanism of the incentive. Section three shows the impact of the incentive program from the aggregate level, at the product level and at the firm level.